Exceptional preservation of comma shrimp from a mid-Cretaceous Lagerstätte of Colombia, and the origins of crown Cumacea. Issue 1916 (27th November 2019) - Luque, Javier; Gerken, Sarah
Abstract : Mesozoic rocks with exceptional preservation of marine arthropods are known worldwide but largely restricted to mid–high latitudes. The scarcity of assemblages with exceptional preservation in low, tropical latitudes greatly limits our understanding of the origins of several modern groups and the evolution of tropical biotas through time. Here, we report the oldest crown Cumacea, or 'comma' shrimp (Arthropoda: Eumalacostraca: Peracarida) with modern familial affinities, from a new mid-Cretaceous (95–90 Ma) Lagerstätte in tropical South America. Cumaceans have one of the poorest fossil records among marine arthropods, despite today being abundant and speciose benthic organisms associated with fine-grained sediments with high fossilization potential. Eobodotria muisca gen. et sp. nov., found in mass accumulation surfaces, preserves with detail the gut, mouth parts, thoracic legs/pereopods, pleopods, uropods bearing setae, antennal flagella and even small eyes bearing ommatidia. These features, rarely preserved in fossil crustaceans, plus the large sample size (greater than 200 individuals, 6–8 mm long), allow us to discuss phylogenetic/systematic aspects and explore possible mechanisms behind their unusual accumulation. Eobodotria bridges an approximately 165 Myr gap in the cumacean fossil record, provides a reliable calibration point for phylogenetic studies and expands our understanding of exceptional preservation in past and present tropical settings.